Synergy between Indoloquinolines and Ciprofloxacin: An Antibiofilm Strategy against Pseudomonas aeruginosa - Emilie Charpentier; Ludovic Doudet; Ingrid Allart-Simon; Marius Colin; Sophie C. Gangloff; Stéphane Gérard; Fany Reffuveille (MDPI AG, 2021)
Antibiotic treatments can participate in the formation of bacterial biofilm in case of under dosage. The interest of indoloquinoline scaffold for drug discovery incited us to study the preparation of new indolo [2,3-b]quinoline derivatives by a domino radical process. We tested the effect of two different "indoloquinoline" molecules (Indol-1 and Indol-2) without antimicrobial activity, in addition to ciprofloxacin, on biofilm formation thanks to crystal violet staining and enumeration of adhered bacteria. This association of ciprofloxacin and Indol-1 or Indol-2 attenuated the formation of biofilm up to almost 80% compared to ciprofloxacin alone, or even prevented the presence of adhered bacteria. In conclusion, these data prove that the association of non-antimicrobial molecules with an antibiotic can be a solution to fight against biofilm and antibiotic resistance emergence.